KAJIAN MAINTENACE PERAWATAN STRUKTUR CANGKANG PINTU GERBANG KEBON BINATANG (MAGASATWA RAGUNAN - JAKARTA SELATAN) - Kurniawan, Arif; Kasman (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
Architecture In general, in terms of the age of the building which is calculated to be 120years, especially the era of structural functions in the building. Therefore, building maintenance andmaintenance work has many benefits, to be precise at the gate building of the Ragunan Zoo, PasarMinggu, South Jakarta which is poorly maintained and neglected and causes reduced communityactivity when passing through the building. Observation of maintenance or maintenance research isrequired in the zoo gate building which has a wide span and a shell structure, with the ancient birdstyle Mentafora architectural concept, seen from the asymmetrical plan form characteristics, theabsence of a terrace surrounding the building, the main gate form is more functioned as an entrancemain, as well as using glass and non-concrete roofs. Greek columns have been abandoned andreplaced with steel structures covered with concrete. Therefore, the potential of Seashell Structures intoday's modern era is not widely known. Maintenance and maintenance aspects are required bothpermanently and non-permanently both in terms of material and equipment. In order to maintain itsfunction, both for the architectural and structure of the building shell as well as in order to bepreserved, it can further enhance its image and the added value of its characteristics, as a culturalheritage and can be an example of modern sustainability building.